Legal Analysis of Family-Owned Companies in Indonesia: Insights from Court Decisions - Almaududi, Almaududi (Jurnal Hukum dan Peradilan, 2024)
Family-owned companies have a significant role in enhancing national competitiveness. However, conflicts that lead to court disputes threaten the sustainability of family-owned companies. It has happened because some decisions still need to provide legal certainty. This research analyzes the legal aspect of family-owned companies in Indonesia, as reflected in several court decisions in Indonesia. The research method employs a qualitative case study approach. The research findings identify the existence of family-owned companies in court decisions; however, there are some difficulties, such as in determining the legal standing of disputing parties, potentially detrimental provisional decisions, and complexities in understanding corporate law, especially regarding General Meetings of Shareholders (GMS), dividends, and inter-organizational relationships as well as internal family disputes. The findings highlight the need for courts to consider the unique characteristics of family-owned companies, which could improve the consistency of court decisions, enhance legal certainty in the business sector, and promote sustainable economic activities.